Peningkatan PHBS dengan Sosialisasi dan Demonstrasi Cuci Tangan “Tepung Selaci Puput” di Sekolah Dasar - Afwadzi, Benny; Hilmy, Muhammad Gama; Nikmah, Alfi; Lutfiana, Dinda Kharisma; Amani, Nailatul; Susanti, Eka Desy (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
At this time, Clean and Healthy Living Behaviors (PHBS) escape the attention of many people. They pay less attention to the cleanliness and health of themselves and their surroundings. Even though this PHBS must be practiced in various places, especially in schools which are places of study for students who are the nation's successors. PHBS in the school setting is a behavior practiced by students, teachers, and school communities as a preventive effort to prevent disease, improve health quality, and serve as a bridge to achieve a healthy environment. This community service's goal is to identify and adapt images of clean and healthy life behavior to elementary school students (SDN) 03 Purworejo, Ngantang, Malang regency. The method in the community service is Participatory Action Research. The approach is promoting healthy socialization and  demonstrations of PHBS at school using proper hand washing with the “Tepung Selaci Puput” style. The socialization and demonstrations are carried out through four stages: Pre-Interaction Stage, Interaction Stage, Demonstration Stage, and Post-Interaction Stage. According to ten PHBS indicators used in this community service, the  community service team found that more than half of the respondents, 57 students, are behaving well in terms of clean and healthy living, while nearly half of the respondents, 38, are behaving badly. Furthermore, after the community service team held socialization and demonstrations of how to wash hands with soap using the “Tepung Selaci Puput” method, most students at SDN 03 Purworejo could practice proper hand washing and increase their PHBS.